RESERVOIR WATER QUALITY MONITORING IN RAWAL LAKE USING GEOINFORMATICS (Pakistan Journal of Science, 2022)
The objective of this study was to assess the potentials of remotely sensed data for estimation of water quality parameters in the water bodies. The assessment was based on the field measurements, laboratory examination and data analysis of hyper spectral data. The hyper spectral datawere integrated into Landsat 7 ETM (Enhance Thematic Mapper). Examination of correlation of simulated Landsat data reveals that multiplicative two band approach by using Band 5 (short wave infrared) and Band 4 (NIR) is best predicator of total dissolved solids (TDS) in water bodies. The ratio Band 5/ Band 4 is also mostly correlated with electrical conductivity. The simple ratio of Band 5 and Band 4 is also used for salinity in water. These three parameters are observed in Band 5 and Band 4 because these three have a strong correlation with each others. For estimation of turbidity multiplicative band approach using (Band1+Band 2/Band 3+ Band 4) was used. The formulas/ algorithms were developed for the study area. The developed algorithms have potential for the estimation of water quality parameters in inland waters. This research work demonstrates an example for the feasibility of remotely sensed data for effective and efficient assessment of total dissolved solids, electrical conductivity, salinity and turbidity in water bodies or reservoirs
Keywords: water quality; electrical conductivity; total dissolved solids; remote sensing